Wilt, 1962 the night of 100 points and the dawn of a new era - Pomerantz, Gary M (Crown, 2005)
On March 2, 1962, in Hershey, Pennsylvania, young and striking athlete Wilt Chamberlain scored 100 points in a game against the New York Knickerbockers. As historic and revolutionary as the achievement was, it remains shrouded in myth. The game was not televised; no New York sportswriters showed up. In telling the story, author Gary M. Pomerantz brings to life a lost world of American sports, tracking down players, fans, journalists, and basketball historians, conducting more than 250 interviews, to recreate the game in painstaking detail. In 1962, the NBA, stepchild to the college game, was searching for its identity. Its teams were mostly white, the number of black players limited by an unspoken quota. Games were played in half-filled arenas, and the players traveled on buses and trains. Into this scene stepped the unprecedented Chamberlain: strong and quick-witted, a seven-footer who played with a colossal will and a dancer's grace.--From publisher description.